Evaluation of an Isolation Program of Hepatitis C Virus Infected Hemodialysis Patients in Some Hemodialysis Centers in Egypt. (31st October 2012) - Soliman, Amin R.; Momtaz Abd Elaziz, Mohamed; El lawindi, Mona I.
Abstract : Introduction . Hepatitis C virus (HCV) infection is a significant cause of morbidity and mortality in hemodialysis (HD) patients. Several studies demonstrated nosocomial transmission of HCV among HD patients. Aim . We aimed to evaluate the isolation program of HCV seropositive patients among a group of Egyptian haemodialysis patients to decrease the incidence of HCV seroconversion. Methods . One hundred and fourteen HCV seronegative patients who were receiving regular haemodialysis in different four haemodialysis units in Egypt. The first group included forty six patients on regular hemodialysis in two centers following strict isolation of the HCV seropositive patients, and the second group included sixty eight patients on regular hemodialysis in the other two centers not following this strict isolation. All these patients were followed up over a period of 36 months. Results . There was a significantly higher incidence of HCV seroconversion of patients on hemodialysis in units not following strict isolation of HCV seropositive patients (42.9%) than those on regular hemodialysis in units following strict isolation (14.8%). Conclusions . In HD units with a high prevalence of HCV+ patients, strict isolation of HCV+ patients in combination with implementation of universal prevention measures can limit the spread of HCV infection in HD patients.